Design Analysis of a Microcontroller Based Automatic Switching System using Passive Infrared Sensor - Okandeji, A. A.; Jagun, Z.O.; Olajide, M. B.; Kabir, M. T. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
Poor management and conservation of public power supply has constantly resulted into wastage of electricity thereby limiting the industrialization process especially in third world countries. To reduce energy wastage in homes, institutions and public places, this paper presents the development of an automatic switch using passive infrared sensor (PIR). Automatic switch is a device that detects the human presence in a predefined area and can turn on the lights or any electrical appliances. Similarly, the device will automatically turn off the lights or any electrical appliance if nobody is present in the area. Using the PIR sensor (for human detection), Light Dependent Resistor (LDR) (to detect night and day), and a microcontroller programmed using Micro-C, a switching circuit that detects humans in a predefined area is investigated. In particular, an automatic switching system using passive infrared sensors to prevent unwarranted wastage of electricity, and also to prevent electricity related hazards which could result from the use of unmonitored electrical appliances is implemented. The research work guarantees less consumption of power, hence, lower utility bills. Also, it allows for more safety in homes, schools, and offices since heavy-duty and high-power equipment that could cause fire e.g. Air-conditioning systems, electric cookers, boilers, electric irons etc, if left unattended to, can be turned off automatically.